The microbiome and gastric carcinogenesis - J. Pereira-Marques; C. Schulz; K. Schütte; C. Figueiredo (Microbiota in Health and Disease, 2020)
Gastric cancer occurs in a small group of patients following chronic infection with Helicobacter pylori. The development of gastric cancer is multifactorial. Current knowledge that a complex microbial community inhabits the stomach has raised the hypothesis that bacteria other than H. pylori may play a role in gastric carcinogenesis. In this paper, we summarize recent results of the characterization of the microbiota at different sites of the gastrointestinal tract, including the stomach. We also review the latest evidence from human studies and from animal models addressing the role of the gastric microbiota in gastric carcinogenesis. Finally, we highlight recent reports that explore the oral and the gut microbiota as potential gastric cancer biomarkers.